Migração, redes e inserção cultural: estudo de caso dos migrantes nordestinos em Anastácio (MS) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
Societies are increasingly multicultural; the fact is due mainly to migration between cities, regions and countries. The patterns of displacement of people often occur cause to the existence of social networks between the cities involved in the migration process, as these networks establish the connection between the points and facilitates the flow of people. To migrate to other places, people carry with them their cultural characteristics (habits, customs, traditions, events) that pass to enter the location where they are established, enabling the emergence of a "his territory" on the other, from its manifestations cultural. Using the analysis through social networks, this paper presents a case study of northeastern migrants Anastácio (MS), where they established their connections to migration and inserted their culture that, even with the mixing with the local cultures, became the higher expression of cultural location.
Keywords: cultura; redes sociais; migração e território; culture; social networks; migration and territory; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA